Proteomics : Introduction to Methods and Applications - Kraj, Agnieszka; Ed (John Wiley & Sons, 2008)
Introduction to Proteomics is written by seasoned researchers with years of practical experience. In addition to comprehensive discussions of the basic concepts, techniques, and applications of the subject, the text also includes an extensive glossary and a chapter containing laboratory exercises and protocols.